Development of a Synthetic Biology Tool to Quantify the Contribution of Protein Components and Protein Interactions Within Transcriptional Regulatory Complexes - Simmons, Kateland (Université d'Ottawa / University of Ottawa, 2019)
We have formed the basis for a synthetic gene regulatory network in S. cerevisiae to assess the relative contribution of proteins and protein interactions to the function of transcriptional regulatory complexes. This gene network contains two synthetic transcriptional regulator (TR) fusion proteins that control transcriptional activation and repression of a reporter expressed by a synthetic promoter. This system can be modulated and quantified specifically by our manipulations since the transcriptional regulators (TRs) are only active when drug induced. In this thesis, I characterized and optimized my gene network to enable accurate measurements of transcriptional regulation. I demonstrated that my synthetic repressor interacts with a selected native transcriptional regulatory complex. Future mutation experiments can be performed to investigate the relative importance that the selected protein interaction plays on transcriptional regulation. New synthetic repressor fusion proteins can be created to study the relative importance of protein interactions between other TRs, making this tool versatile. This tool will allow us to quantify interactions and gain a deeper understanding of the complicated mechanisms controlling transcriptional regulation.
Keywords: Protein components; Protein interactions